ASSESSING STUDENT'S ENGLISH VOCABULARY ABILITY USING SENTENCE CONSTRUCTION TEST - Ida Bagus Nyoman Mantra; Ni Luh Sukanadi; I Nyoman Adi Susrawan; I Nyoman Suwandi; I Nyoman Suparsa (International Journal of Applied Science and Sustainable Development (IJASSD), 2023)
Vocabulary development is critical from both a theoretical and a practical point of view. Vocabulary is a central factor in the process of language learning. This research is based on the idea that students are required to use English in daily interactions in the school's language program. Therefore, learning English vocabulary is crucial for improving students’ language skills. Teachers must know the students' abilities before conducting the learning activities. This study used ex post facto research design to reveal students’ vocabulary ability by conducting sentence construction tests. The study found that students' vocabulary is at a sufficient level. Therefore, students are required to improve their vocabulary to a higher level. This study highlights that various vocabulary activities should be intensified in the classroom to build up students’ active vocabulary and enable them to speak communicatively.